A Comprehensive Review of Semiconductor-Type Gas Sensors for Environmental Monitoring - Nayyar, Anand; Puri, Vikram; Le, Dac-Nhuong (Review of Computer Engineering Research, 2016)
In this paper a review of different semiconductor-type gas sensors is presented. The different types of gas sensors from various companies like Hanwei, Libelium, Sandbox Electronics and Sensor Tech SGX are discussed along with their technical specifications. Environment is surrounded by various sorts of gases cum pollutants and it is utmost necessary to keep a efficient check on them as these gases can cause trouble to the health of human beings and pollute environment drastically. The main objective of this research paper is to present all sorts of gas sensors which are based on semiconductors and to generate awareness regarding which sensor is best for which detection. However, for more improved sensitivity and selectivity for these sensors, future trends and outlook for researchers is also suggested. The paper can also act as base for researchers to get hold of these sensors to develop a market ready product like drone or robot for Environmental Gas Detection.